2010
DOI: 10.1063/1.3459125
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between like-charged polyelectrolyte-colloid complexes in electrolyte solutions: A Monte Carlo simulation study in the Debye–Hückel approximation

Abstract: We study the effective interaction between differently charged polyelectrolyte-colloid complexes in electrolyte solutions via Monte Carlo simulations. These complexes are formed when short and flexible polyelectrolyte chains adsorb onto oppositely charged colloidal spheres, dispersed in an electrolyte solution. In our simulations the bending energy between adjacent monomers is small compared to the electrostatic energy, and the chains, once adsorbed, do not exchange with the solution, although they rearrange o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 58 publications
(105 reference statements)
4
34
0
Order By: Relevance
“…(2) is always attractive (negative) also for like-charged particles. The presence of this attractive term is consistent with the results of Poisson-Boltzmann equation approaches and simulations [19,54,55], pointing out the existence of a short range attraction between polyelectrolyte-decorated macroions. The term "short range" is well justified since the decaying length of the attractive term (2Ä) −1 is one half of the Debye screening length that sets the scale for the screened electrostatic interactions.…”
Section: Theoretical and Phenomenological Backgroundsupporting
confidence: 85%
See 2 more Smart Citations
“…(2) is always attractive (negative) also for like-charged particles. The presence of this attractive term is consistent with the results of Poisson-Boltzmann equation approaches and simulations [19,54,55], pointing out the existence of a short range attraction between polyelectrolyte-decorated macroions. The term "short range" is well justified since the decaying length of the attractive term (2Ä) −1 is one half of the Debye screening length that sets the scale for the screened electrostatic interactions.…”
Section: Theoretical and Phenomenological Backgroundsupporting
confidence: 85%
“…The relevance of bridging and/or the presence of bridging events in a variety of colloid/polyelectrolyte mixtures has been characterized experimentally by Borkovec et al [34] who pointed out that, in systems with small polymer/colloid size ratio, individual bridging events could be only rarely identified from the retraction part of the force profiles measured by AFM, concluding that bridging forces are unimportant in these systems. Monte Carlo simulations [19] with colloids having the same nominal surface charge density of pure DOTAP liposomes and fully ionized polyelectrolyte chains have shown that the non-DLVO attractions are dominated by charge patch attraction rather than bridging, whose onset has been detected only under conditions of high overcharging of the particles, i.e. where the adsorbed polyelectrolyte-layers are characterized by several protruding chains and dangling ends.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Surprisingly enough, those authors found that "the eventual aggregation of the two complexes occurs with the antiparallel orientation of the dipoles" and remark that "this antiparallel orientation of the dipole doublet signals the absence of a longrange dipole-dipole attractive contribution to the mean-force interparticle potential [32]." All this qualitatively agrees with our work .…”
Section: Discussionsupporting
confidence: 82%
“…At the end of the present work, it has been published an interesting paper on a realistic system which has strong similarities with our model and thus provides it with more physical plausibility. It deals with a fluid of charged colloidal spheres, whose surface is decorated with a thin and nonuniform layer of adsorbed polyelectrolytes [32]. On varying the ionic strength of the electrolyte solution, the screening length κ −1 D can become short compared to the size of the colloidal particles.…”
Section: Discussionmentioning
confidence: 99%